2017
DOI: 10.3390/educsci7010027
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Digital Competency among Student Teachers: Contributing to the Development of Student Teachers’ Instructional Self-Efficacy in Technology-Rich Classrooms

Abstract: Adequate self-efficacy is useful for motivating individuals to engage in continued improvement. This study explores the potential antecedents of instructional self-efficacy beliefs among Norwegian student teachers attending a programme for secondary school teachers. The most important finding was the strong association between the student teachers' perceptions of digital competency to resolve challenges relating to information and communication technology (ICT) in schools and their instructional self-efficacy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0
12

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 49 publications
(32 reference statements)
7
67
0
12
Order By: Relevance
“…Whereas, the results show that majority of TVET teachers were more than 40 years of age, where very few respondents represented the digital generation. Hence, the study reported that the younger teachers were higher skills particularly in Word processing then Spreadsheet and databases, this results agreed with (Alazam et al, 2012;Bennett et al, 2008;Elstad & Christophersen, 2017). Therefore, younger teachers were more associative with ICT usage in the TVET institutions as reported in the findings.…”
Section: Research Question 1: Differences Between Tvet Teachers' Ict supporting
confidence: 80%
See 3 more Smart Citations
“…Whereas, the results show that majority of TVET teachers were more than 40 years of age, where very few respondents represented the digital generation. Hence, the study reported that the younger teachers were higher skills particularly in Word processing then Spreadsheet and databases, this results agreed with (Alazam et al, 2012;Bennett et al, 2008;Elstad & Christophersen, 2017). Therefore, younger teachers were more associative with ICT usage in the TVET institutions as reported in the findings.…”
Section: Research Question 1: Differences Between Tvet Teachers' Ict supporting
confidence: 80%
“…(Demetriadis et al, 2003) state that "if educators do not have sufficient abilities for handling a computer, improbably they will be able to incorporate technology into their classroom teaching". (Elstad & Christophersen, 2017;Hatlevik, Scherer, & Christophersen, 2017) reported from their research that 56.6% of upper secondary students believe their professors have no knowledge of computer use. Keeping that overwhelming statistic in mind, assessing the basic levels of current teacher engagement with computer skills such as word processing (Hyland, 1990), handling files, spreadsheets database, e-mail and uses of social media through an internet connectivity needs to be the starting points for this study.…”
Section: The Impact Of Ict Use On Tvet Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…More generally, SEP helps the individual choose and control their actions (effort expenditure, persistence), but also their thoughts (positive or negative), their feelings (emotional reactions to obstacles), their motivation, etc. Self-efficacy is useful for motivating individuals toward continued improvement (Elstad and Christophersen 2017). People with high SEP thus approach difficult tasks as challenges to take on rather than threats to avoid.…”
Section: The Effects Of Sepmentioning
confidence: 99%